2014
DOI: 10.1097/hp.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Combined Drug and Surgery Treatment of Plutonium-contaminated Wounds

Abstract: There is an important requirement following accidental actinide contamination of wounds to limit the dissemination and retention of such alpha-emitting radionuclides. To reduce wound and systemic contamination, treatment approaches include chelation therapy with or without wound excision. However, it has been hypothesized that wound excision could lead to increased contaminant release and systemic organ retention. This study in the rat addresses this question. Anesthetized rats were contaminated with plutonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, it would be interesting to test these products after washing with TR, for example, in order to try to remove the remaining skin-associated activity. It would also be interesting to include DTPA in the dressing either in gel form or simply by injection into the structure, in addition to testing in an actinide-contaminated wound model with or without surgery (Griffiths et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be interesting to test these products after washing with TR, for example, in order to try to remove the remaining skin-associated activity. It would also be interesting to include DTPA in the dressing either in gel form or simply by injection into the structure, in addition to testing in an actinide-contaminated wound model with or without surgery (Griffiths et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The CED averted due to excision calculated in this paper assumes that the increase in dose to the systemic organs, due to release of activity by excision, is negligible. In fact, an animal study (Griffiths et al 2014) found that urinary Pu excretion was increased after partial wound excision, but this was not accompanied by further retention of Pu in bone or liver.…”
Section: Resultsmentioning
confidence: 99%
“…injection (Bistline et al 1972, Piechowski et al 1989. Using this model the efficacy of surgical excision and different DTPA administration protocols (single or repeated, and local or systemic) have been assessed on liver and skeleton retention and urinary excretion of Pu (Griffiths et al 2014a, Griffiths et al 2014b). Data analyses have been mostly descriptive and based on central values (means and standard deviations) over groups of animals with same contamination conditions and treatment regimens.…”
Section: Introductionmentioning
confidence: 99%